PELATIHAN BRANDING MARKETING SARANG’E KOPI DI DUSUN MADUARJO NGAJUM MALANG - Ana Nurwakhidah (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2022)
Micro, Small and Medium Enterprises (UMKM) have an important role in improving the Indonesian economy. There are quite a number of UMKM actors in Maduarjo Hamlet, Babadan Village, Ngajum District, considering that the area is one of the well-known coffee-producing areas in Malang Regency. In increasing the knowledge of UMKM actors in Dusun Maduarjo regarding branding, it is necessary to hold Branding Marketing Training activities considering that Branding is very important to determine the brand image in the production of the goods produced. The method of implementing this Branding Marketing training is the lecture method/discussion of materials related to Branding and Marketing. The result of this branding marketing training activity is that the branding training program is a very important benchmark in marketing a product. Maduarjo villagers hope that the next training and socialization will teach them how to make production and packaging permits that are not inferior to other local brands.